Astronomy Lab I: Photometric Experiments for Physics Students - Reza Rezaei (Iranian Journal of Astronomy and Astrophysics)
As physics laboratories are an integral part of the physics education across the globe, astronomy laboratories are also a necessary part of the astronomy education. However there have been only theoretical astronomy and astrophysics in Iranian universities. We present for the first time a new laboratory course on observational astronomy for bachelor and master students. In this course, students performed observational experiments and learned how to analyze astronomical data. Data are transformed from the camera RAW to the FITS format and later analyzed using Python AstroPy packages. In Astronomy Lab I, students learned to polar align equatorial mounts, measure the read and shot noises, estimate the spatial resolution in long exposure images, measure the solar limb darkening, stack a number of images to get a high signal to noise final image, calculate magnitude using aperture photometry, retrieve the absorption coefficient for each filter, correct for the atmospheric extinction and draw a Hertzsprung-Russell (HR) diagram for open clusters.